Post-materiality in the Andes: Andean performative spaces in Yuyachkani - Gonzales Duran, Pedro de Jesus (Latin American Theatre Review, 2022)
In this article, I analyze two iconic one-actor plays, Adios Ayacucho (1990) and Rosa Cuchillo (2002), written and performed by the theatre collective Grupo Cultural Yuyachkani. I propose that, in both plays, non-human elements, in collaboration with the human bodies, develop the memory process to overcome the trauma produced by Internal Conflict in Peru (1980-2000). Both pieces present the story of a dead body returning to the human (living) world to accomplish a mission, to recover Canepa's own body in Adios Ayacucho, or to find a missing son in Rosa Cuchillo. However, this purpose will not be possible without the intervention of non-human elements. Through a discussion of the Andean notion of yanantin, a complementary opposition process between all existent components; Tara Daly's concept of vital materialism; and Jane Beneath's idea of actant, in the essay, I examine the role of the space as a sum of non-human elements that intervened in the memory process. These spaces analysis opens new interpretations of Peruvian political and theatrical stages through Andean knowledge as a decolonizing way to understand memory.